Jogos empíricos de entrada: uma aplicação ao setor bancário brasileiro - Jucá, Jader Garcia (2017)
The Brazilian banking sector is very concentrated, we have that 68% of the total assets are held by five banks. Another feature of this sector is the participation of public banks, they held 42% of assets. This paper seeks to investigate the competition of the Brazilian banking sector through the methodology of empirical games. Entry into the banking sector is modeled as a simultaneous entry game with incomplete information. The model transforms actions of competition between banks into entry probabilities, showing the possibility of a bank entering in a given market and not the entry in fact. The decisions of the banks revolve around the existing trade-off between greater competition and the desire for certain market characteristics. The model is developed for the six largest banks in assets and includes controls for greater robustness. The results show that the North and Northeast regions are the less attractive for banking activity, while the South and Southeast are the most attractive. Another result obtained shows that the other banks benefit from the presence of CAIXA, which is not the case for Banco do Brasil and the private banks.